Fetal drug syndromes. Issue 638 (December 1978) - Gordon, Neil
Abstract : Certain drugs which affect fetal development are considered. Phenytoin taken during pregnancy may result in infants who remain mentally and physically retarded, with abnormal craniofacial appearance and limb defects. A boy with such a syndrome is reported. Trimethadione is another drug which has been said to be teratogenic, and to cause a typical phenotype which is described. The fetal alcohol syndrome is now well recognized and has similar features to those related to anti-epileptic drugs taken during pregnancy. A high level of suspicion of possible associations between congenital defects and drugs must be maintained.